Frommer's new orleans ebook - Schwam, Diana K. (Frommer's Color Complete Guides., 2011)
Full-color throughout Free full-color, foldout map Insider advice on the best way to experience Mardi Gras, Jazz Fest, and all of the city's famous music and nightlife. Where to find the absolute best food in the Big Easy, from upscale Creole dining in the French Quarter to po' boys in the Central Business District to seafood and New American cuisine in the Garden District. Insightful commentary on New Orleans's fantastic historical heritage, as wells as on its extraordinary museums, art galleries, and architecture. Opinionated reviews. No bland descriptions and lukewarm recommendations. Our expert writer is passionate about New Orleans. Exact prices listed for every establishment and activity--no other guides offer such detailed, candid reviews of hotels and restaurants. We include the very best, but also emphasize moderately priced choices for real people. User-friendly features including star ratings and special icons to point readers to great finds, excellent values, insider tips, best bets for kids, special moments, and overrated experiences.